Method for manufacturing geopolymer foam

JP7630402B2Active Publication Date: 2025-02-17JSP CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021161014
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-09-30
Publication Date
2025-02-17
Estimated Expiration
2041-09-30

AI Technical Summary

Benefits of technology

【0009】 本発明のジオポリマー発泡体の製造方法は、骨材としてジオポリマー粉体を使用することでリサイクル性を向上させるとともに、優れた強度を有するジオポリマー発泡体を製造することできる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007630402000001
    Figure 0007630402000001
  • Figure 0007630402000002
    Figure 0007630402000002
  • Figure 0007630402000003
    Figure 0007630402000003
Patent Text Reader

Abstract

To provide a method for producing a geopolymer foam, which uses a geopolymer powder as an aggregate to improve recyclability, and can produce the geopolymer foam that is easy to produce and has excellent strength.SOLUTION: A method for producing a geopolymer foam includes: reacting an aluminosilicate with an alkali metal silicate in the presence of an aggregate to form a geopolymer-containing reaction slurry; and foaming the reaction slurry with a foaming agent to form a geopolymer foam having a number of bubbles, wherein the aggregate contains a geopolymer powder; an average particle size of the geopolymer powder is 30 to 500 μm; and in the geopolymer powder, a volume fraction of particles each having a particle diameter of 10 μm or less is 5% or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing geopolymer foam. [Background technology]

[0002] Geopolymers are inorganic polymers produced by reacting aluminosilicates with alkali metal silicates, and have been attracting attention as environmentally friendly materials.

[0003] Specifically, this geopolymer has a tetrahedral structure formed from SiO4 and AlO4, and has a structure in which cations that compensate for the negative charge of AlO4 are contained in the network of the tetrahedral structure.

[0004] For example, U.S. Patent No. 5,399,633 describes a geopolymer composite having a particulate ceramic filler and a geopolymer binder that constitutes at least 2% by weight of the material in a composite article formed from the composite material. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Special Publication No. 2008-543701 Summary of the Invention [Problem to be solved by the invention]

[0006] On the other hand, for example, when cutting a geopolymer foam into a product or processing it to be surface-finished, scraps, scraps, powder, etc. of the geopolymer foam are generated. These scraps, etc. of the geopolymer foam cannot be formed into a shape as a product and are discarded, which can reduce the recyclability of the geopolymer foam or reduce the final product yield of the geopolymer foam.

[0007] The present invention has been made in consideration of the above circumstances, and has an objective of providing a method for producing a geopolymer foam that improves recyclability, is easy to produce, and has excellent strength. It is an object of the present invention to provide a method for producing a geopolymer foam. [Means for solving the problem]

[0008] In order to solve the above problems, the method for producing geopolymer foam of the present invention is characterized as follows. <1> The method for producing a geopolymer foam of the present invention comprises reacting an aluminosilicate with an alkali metal silicate in the presence of an aggregate to form a reaction slurry containing a geopolymer, and foaming the reaction slurry with a foaming agent to form a geopolymer foam having a large number of bubbles. the aggregate comprises geopolymer powder; The average particle size of the geopolymer powder is 30 to 500 μm; The geopolymer powder is characterized in that the volume fraction of particles with a particle diameter of 10 μm or less is 5% or less. <2> The above <1> The method for producing geopolymer foam of the present invention is characterized in that the volume fraction of particles having a particle diameter of 200 μm or more in the geopolymer powder is 85% or less. <3> The above <1> or <2> In the method for producing a geopolymer foam of the invention, the geopolymer powder is a powder obtained by pulverizing a geopolymer foam. Effect of the Invention

[0009] The method for producing a geopolymer foam of the present invention can improve recyclability by using geopolymer powder as an aggregate, and can produce a geopolymer foam having excellent strength. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] In the production of geopolymer foam, when geopolymer powder is used as an aggregate, the viscosity of the reaction slurry during the reaction tends to increase and the strength of the geopolymer foam tends to decrease. However, the inventors have discovered that this problem can be solved by adding geopolymer powder having certain characteristics as an aggregate, and have completed the present invention.

[0011] Hereinafter, one embodiment of the method for producing a geopolymer foam of the present invention will be described. The method for producing a geopolymer foam of the present invention comprises reacting an aluminosilicate with an alkali metal silicate to form a reaction slurry containing a geopolymer, and foaming the reaction slurry with a foaming agent to form a geopolymer foam having a large number of bubbles.

[0012] (Aluminosilicate) In the method for producing a geopolymer foam of the present invention, an aluminosilicate is used. The aluminosilicate is a compound having a structure in which some of the silicon atoms in a silicate are replaced with aluminum atoms.

[0013] The SiO2 (silicon dioxide) content in the aluminosilicate is preferably 20% by mass or more and 80% by mass or less, more preferably 30% by mass or more and 70% by mass or less. When the SiO2 content is in this range, the produced geopolymer foam is likely to form a good cell structure with a large number of bubbles. The SiO2 content and the Al2O3 content in the aluminosilicate, which will be described later, can be determined by quantifying each element using a fluorescent X-ray analyzer (e.g., EA6000V manufactured by Hitachi High-Tech Science).

[0014] (Specific examples) Suitable examples of aluminosilicates include clay minerals such as beidellite, bentonite, metakaolin, kaolinite, halloysite, montmorillonite, pyrophyllite, vermiculite, mica, chlorite, saponite, sepiolite, and acid clay, fly ash, silica fume, and other silicate minerals containing aluminum, and calcined aluminosilicates are preferred, particularly metakaolin. These substances can be commercially available, and one or more of these may be used in combination. In addition, the aluminosilicate is preferably in the form of a powder. These substances can be appropriately ground and classified, and a specific fraction can be used to prepare an aluminosilicate of a desired composition.

[0015] (Metakaolin) Among them, a particularly preferred metakaolin is a compound represented by the chemical formula Al2O3·2SiO2, and the ratio of metakaolin in the aluminosilicate is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more. When the ratio of metakaolin in the aluminosilicate is within the above range, a good cell structure with a large number of bubbles is easily formed in the geopolymer foam, and a geopolymer foam with excellent strength can be stably obtained.

[0016] In addition, the average particle size of these aluminosilicates is preferably 0.1 μm to 50 μm, more preferably 0.3 μm to 30 μm, and even more preferably 0.5 μm to 10 μm. When the average particle size is within this range, the produced geopolymer foam has a good cell structure.

[0017] (particle size measurement) The average particle size of the aluminosilicate can be measured by a laser diffraction scattering method. Specifically, the average bubble size can be calculated based on the volume-based particle size distribution measured by the laser diffraction scattering method. The average particle size refers to the diameter of a virtual sphere having the same volume as the particle.

[0018] (Al content) The lower limit of the Al2O3 content in the aluminosilicate is preferably 20 mass% or more, more preferably 30 mass% or more, based on the total mass of the aluminosilicate. The upper limit of the Al2O3 content in the aluminosilicate is preferably 70 mass% or less, more preferably 50 mass% or less, based on the total mass of the aluminosilicate. When the Al2O3 content is within this range, the strength of the geopolymer foam is easily increased.

[0019] (alkali metal silicate) In the method for producing the geopolymer foam of the present invention, alkali metal silicates and the like are used, and one or more of these can be used. Examples of alkali metal silicates include potassium silicate, sodium silicate, and lithium silicate, which form a highly alkaline aqueous solution when dissolved in water.

[0020] By reacting an alkaline aqueous solution of this alkali metal silicate with an aluminosilicate, cations such as Al can be eluted from the aluminosilicate and silicic acid monomers can be produced. The alkali metal silicate serves as a source of silicic acid monomers that form geopolymers by polycondensation.

[0021] (Potassium Silicate) Among them, the alkali metal silicate is preferably potassium silicate. In order to adjust the hydrogen ion concentration (pH) of the aqueous solution and obtain an aqueous solution exhibiting a desired alkalinity, an alkali metal hydroxide such as potassium hydroxide or sodium hydroxide can be added to the aqueous solution of the alkali metal silicate.

[0022] The molar ratio (SiO2 / K20 ratio) in potassium silicate is preferably 1 to 5, more preferably 1.5 to 4.5, and even more preferably 3 to 4. By setting the molar ratio within the above range, the strength of the geopolymer foam can be further increased.

[0023] (Potassium silicate aqueous solution) The alkali metal silicate is preferably added as an aqueous solution. For example, the concentration of the alkali metal silicate in the aqueous solution of the alkali metal silicate is preferably 20% by mass or more and 60% by mass or less, more preferably 22% by mass or more and 50% by mass or less, and even more preferably 25% by mass or more and 45% by mass or less. When the concentration of the alkali metal silicate is within this range, the foam moldability of the reaction slurry in which the aluminosilicate and the aqueous solution of the alkali metal silicate are mixed can be improved.

[0024] (Potassium hydroxide added) In particular, in order to adjust the pH of the reaction slurry and promote the reaction between the aluminosilicate and the alkali metal silicate, 10 to 90 parts by mass of potassium hydroxide can be added per 100 parts by mass of the alkali metal silicate, and it is more preferable to add 50 to 80 parts by mass of potassium hydroxide.

[0025] (aggregate) In the method for producing geopolymer foam of the present invention, geopolymer powder is included as an aggregate (hereinafter, the geopolymer powder added as aggregate may be simply referred to as geopolymer powder (A)). It is preferable that the aggregate contains geopolymer powder (A) as a main component, and more preferably, the content of geopolymer powder (A) in the aggregate is 90 mass% or more, and even more preferably, the content of geopolymer powder (A) in the aggregate is 95 mass% or more.

[0026] (Geopolymer powder (A)) The geopolymer powder (A) is preferably a powder obtained by crushing recycled materials such as scraps and scraps of the geopolymer foam of the present invention. The geopolymer powder (A) acts as an aggregate in the geopolymer foam, and can improve the strength of the geopolymer foam and can improve the recyclability during the production of the geopolymer foam. The geopolymer powder (A) exists as an aggregate, and is distinguished from the geopolymer obtained by reacting the aluminosilicate and the alkali metal silicate, and is added separately to the reaction slurry. In addition, the geopolymer powder (A) is thought to suppress the heat generation of the reaction slurry in the reaction slurry during the geopolymer production process.

[0027] (Average particle size) The geopolymer powder (A) has an average particle size of 30 to 500 μm, preferably 50 to 300 μm. When the average particle size of the geopolymer powder (A) is within this range, the viscosity of the reaction slurry is good, and the reaction slurry is suitable for generating geopolymers and constructing a cellular structure, and a geopolymer foam having excellent strength can be stably obtained.

[0028] (particle size distribution) The average particle size of the geopolymer powder (A) can be measured by a laser diffraction scattering method. Specifically, a volume-based particle size distribution is obtained by measuring the volume of the powder by a laser diffraction scattering method. The average particle size is the diameter of a virtual sphere having the same volume as the particle.

[0029] (Small particle size components) In addition, the volume ratio of particles having a particle diameter of 10 μm or less in the geopolymer powder (A) is 5% or less. When the volume ratio of particles having a particle diameter of 10 μm or less is 5% or less, the viscosity of the reaction slurry in which the geopolymer is formed does not increase excessively, and the reaction slurry becomes suitable for constructing a cellular structure. In addition, the reaction slurry becomes suitable for constructing a cellular structure capable of forming a foam having excellent strength, and a geopolymer foam having excellent strength can be stably obtained. In particular, when a shear force such as stirring is applied to the reaction slurry in which the geopolymer generated by the reaction of the aluminosilicate and the alkali metal silicate and the geopolymer powder (A) are dispersed, the reaction slurry is likely to suddenly exhibit a high viscosity. When such a phenomenon is observed, it becomes difficult to form stable bubbles when the reaction slurry is foamed. On the other hand, when the viscosity of the reaction slurry is adjusted by adding water to suppress the increase in viscosity, fine cracks due to the evaporation of water are easily formed in the bubble walls during hardening, and it becomes difficult to obtain a geopolymer foam having excellent strength. From the viewpoint of preventing these, the volume ratio of particles having a particle diameter of 10 μm or less in the geopolymer powder (A) is preferably 4.7% or less, and more preferably 4.5% or less.

[0030] (Large particle size components) Furthermore, the volume fraction of particles having a particle diameter of 200 μm or more in the geopolymer powder (A) is preferably 85% or less. When the volume fraction of particles having a particle diameter of 200 μm or more is 85% or less, cracks originating from large particle diameter components are unlikely to form, and a geopolymer foam having excellent strength can be stably obtained. From the above viewpoint, the volume fraction of particles having a particle diameter of 200 μm or more in the geopolymer powder (A) is more preferably 10 to 80%, and more preferably 20 to 60%.

[0031] (Amount of geopolymer powder (A)) The amount of the geopolymer powder (A) is preferably 5% by mass or more and 50% by mass or less, more preferably 10% by mass or more and 45% by mass or less, and even more preferably 20% by mass or more and 40% by mass or less, based on 100% by mass of the total of the aluminosilicate, the alkali metal silicate, and the geopolymer powder (A). When the amount of the geopolymer powder (A) is within this range, a good geopolymer matrix structure is formed, and the geopolymer powder acts as an aggregate, so that a cellular structure of a geopolymer foam having improved strength can be stably obtained.

[0032] (Reaction slurry) In the method for producing geopolymer foam of the present invention, an aluminosilicate is reacted with an alkali metal silicate to form a reaction slurry containing a geopolymer. By reacting the aluminosilicate with the alkali metal silicate in an aqueous solution (slurry), aluminum ions are dissolved in the aqueous solution and silicic acid monomers (silicic acid, Si(OH)4) are generated. It is believed that the silicic acid monomers thus generated and cations are polycondensed to form a geopolymer having a polymer network with a tetrahedral structure of SiO4·AlO4.

[0033] Specifically, for example, a powder raw material mixture such as an aluminosilicate, a geopolymer powder, an alkali silicate, and water are mixed, and preferably the powder raw material mixture is mixed with an aqueous alkali silicate solution to react the aluminosilicate with the alkali metal silicate to form a reaction slurry containing a geopolymer.

[0034] The term "slurry" refers to a fluid in which the solid components of the particles of the powder raw material mixture, the geopolymer powder, and the geopolymer generated by the reaction of the aluminosilicate and the alkali metal silicate are dispersed in water. In this reaction slurry, it is not necessary that the aluminosilicate and the alkali metal silicate react completely to form the geopolymer, but it is sufficient that the formed geopolymer exists as a part of the reaction slurry. The ratio of the solid components of the slurry is preferably 30% to 80%, more preferably 40% to 60%. The slurry medium is mainly composed of water, but water-soluble alcohols may be added as secondary components.

[0035] (Alkali / aluminosilicate ratio, etc.) When forming the reaction slurry, it is preferable to add 10 to 500 parts by mass of the alkali silicate, and preferably 20 to 400 parts by mass of the alkali silicate to a total of 100 parts by mass of the aluminosilicate, the alkali metal silicate, and the geopolymer powder. By adding the amount in the above range, it is possible to homogeneously disperse each component in the foamable composition while increasing the strength of the resulting geopolymer foam.

[0036] (Reaction process) The aluminosilicate and the alkali metal silicate are uniformly dispersed in the reaction slurry, and the aluminosilicate and the alkali metal silicate react to form a geopolymer. The reaction is thought to occur when the aluminosilicate is added to the alkali metal silicate aqueous solution, but in order to carry out the reaction more efficiently, it is preferable to heat the reaction slurry. When the reaction slurry is heated, the decomposition type foaming agent described later may be decomposed by heating to foam, or the reaction and foaming may proceed simultaneously in parallel.

[0037] (Al / Si ratio) In the reaction step of the aluminosilicate and the alkali metal silicate, the molar ratio Si / Al of Si to Al in the reaction slurry is preferably 0.1 to 10, more preferably 0.5 to 5, and even more preferably 1 to 3. When the molar ratio Si / Al of the mixture is within this range, the generated geopolymer foam can have an adequate amount of exchangeable cations and can form a good cell structure.

[0038] (viscosity) The viscosity of the reaction slurry obtained by mixing the aluminosilicate and the alkali silicate aqueous solution and reacting the aluminosilicate with the alkali metal silicate, as measured by the method described below, is preferably 5 Pa·s to 60 Pa·s, more preferably 10 Pa·s to 50 Pa·s. In particular, if the viscosity of the reaction slurry is within the above range, the viscosity is easy to control, and a sudden increase in viscosity due to the application of shear force to the slurry in which the geopolymer powder (A) is dispersed does not occur, making it easy to form bubbles.

[0039] (Other additives) In the method for producing a geopolymer foam of the present invention, additives such as a bubble opener, reinforcing fiber, and aggregates other than geopolymer powder can be added to the powder raw material mixture of aluminosilicate and geopolymer powder. The reinforcing fiber can be added for the purpose of improving the strength of the geopolymer foam and preventing cracks. Examples of reinforcing fibers include vinylon fiber, polypropylene fiber, aramid fiber, acrylic fiber, rayon fiber, carbon fiber, glass fiber, potassium titanate whisker, alumina fiber, steel wool, and slag wool. The strength of the geopolymer foam can be increased by adding reinforcing fibers.

[0040] The amount of other materials added is not particularly limited as long as it is within the range in which the intended object of the present invention can be achieved, but it is preferably 20 parts by mass or less, and more preferably 10 parts by mass or less, per 100 parts by mass of the total of the aluminosilicate, alkali metal silicate, and geopolymer powder. (Foaming process)

[0041] In the method for producing a geopolymer foam of the present invention, a geopolymer is formed in the reaction slurry, and a foaming agent is added to the reaction slurry to foam the foaming agent, thereby obtaining a geopolymer foam having a large number of bubbles.

[0042] (foaming agent) Examples of the foaming agent include decomposition type foaming agents such as hydrogen peroxide, sodium peroxide, potassium peroxide, and sodium perborate, as well as non-ferrous metal powder. Examples of the non-ferrous metal powder include aluminum powder. Among these, it is preferable to use hydrogen peroxide or non-ferrous metal powder as the foaming agent, and it is more preferable to use hydrogen peroxide.

[0043] (Hydrogen peroxide) In addition, when hydrogen peroxide is used as a foaming agent, it is preferable to use it as hydrogen peroxide water. In this case, from the viewpoint of easily obtaining a geopolymer foam having a good cell structure, the concentration of hydrogen peroxide in the hydrogen peroxide water is preferably 10% by mass or more and 50% by mass or less, more preferably 20% by mass or more and 40% by mass or less.

[0044] The amount of foaming agent to be added is not particularly limited, but for example, when hydrogen peroxide is added, the amount is preferably 0.1% by mass or more and 10% by mass or less, more preferably 0.3% by mass or more and 3% by mass or less, and even more preferably 0.5% by mass or more and 2% by mass or less, relative to 100 parts by mass of the total of the aluminosilicate, the alkali metal silicate, and the geopolymer powder. This allows the reaction slurry to be sufficiently foamed, and a geopolymer foam having a good cell structure can be stably obtained.

[0045] (Bubble Opener) Furthermore, in the foaming step, the reaction slurry is foamed to form a large number of bubbles in the reaction slurry of the aluminosilicate and the alkali silicate, and the bubbles can be opened. As the bubble-opening agent, for example, microorganisms such as yeast and algae, proteins, surfactants, etc. can be used. Among them, the bubble-opening agent is preferably yeast (e.g., dry yeast). The amount of yeast added is preferably 0.1 to 2 parts by mass, more preferably 0.2 to 1 part by mass, based on 100 parts by mass of the total of the aluminosilicate, the alkali metal silicate, and the geopolymer powder.

[0046] (heating) In the method for producing a geopolymer foam of the present invention, the reaction slurry containing the foaming agent is heated to further promote the reaction between the aluminosilicate and the alkali metal silicate, and the foaming agent is foamed to form bubbles, resulting in a geopolymer foam having a large number of bubbles.

[0047] The temperature during the heating depends on the foaming agent used, but in the case of a decomposition type foaming agent, it is preferable to heat to near the decomposition temperature of the foaming agent. In particular, when hydrogen peroxide water is used as the foaming agent, the heating temperature is preferably 50 to 80° C. The reaction by heating and foaming may be carried out simultaneously in parallel.

[0048] (molding) The reaction slurry is placed in a mold, and the mold is heated to further react the aluminosilicate with the alkali metal silicate and to foam the foaming agent, resulting in a molded product of geopolymer foam having the shape of the mold. By employing various molding methods, it is possible to mold the product into a desired shape.

[0049] For example, when a casting method is employed, the bubbles formed by foaming the reaction slurry grow within about 30 minutes to 1 hour after the addition of the foaming agent, and form a cellular structure.

[0050] (Foam molded body) In the method for producing a geopolymer foam in the present invention, unlike physical foaming in which bubbles are formed by stirring, etc., the bubbles are gradually grown by adding a foaming agent, so that the bubbles are less likely to be finer and the bubble diameter is less uneven, making it possible to obtain a foam with a relatively uniform bubble structure. In addition, the moderate increase in viscosity of the reaction slurry by adding a specific geopolymer powder also contributes to the stabilization of the bubbles, making it easier to construct the bubble structure of the geopolymer foam.

[0051] The geopolymer foam has an apparent density of 100 kg / m 3 More than 500kg / m 3 From the viewpoint of light weight, the apparent density is preferably 105 kg / m or less. 3 More than 300kg / m 3 More preferably, it is 110 kg / m or less. 3 More than 200kg / m 3 It is even more preferable that:

[0052] The geopolymer foam preferably has a maximum bubble diameter of 1 mm or more and 10 mm or less. If a bubble structure having such a bubble diameter can be formed, it becomes easier to form a bubble wall having excellent strength. From the above viewpoint, the maximum bubble diameter is preferably 2 mm or more and 5 mm or less.

[0053] (Firing) Furthermore, by firing the obtained foamed molded body, a geopolymer foamed fired body can be formed, which makes it possible to prevent dimensional changes at high temperatures. The method for producing geopolymer foam of the present invention is not limited to the above embodiment. EXAMPLES

[0054] Hereinafter, the method for producing a geopolymer foam of the present invention will be described with reference to examples, but the present invention is not limited to the following examples.

[0055] Raw Materials for Forming Geopolymer Foam The following raw materials were used to make the geopolymer foam: Aluminosilicate: Metakaolin (Imerys: Argical M1200S, crystallinity 0%) Alkali metal silicate: Potassium silicate (manufactured by Nippon Chemical Industry Co., Ltd.: 2K potassium silicate) Aggregate: Geopolymer powder (ground geopolymer foam products 1 to 3) shown in Table 1 Bubble nucleating agent: Talc (Matsumura Sangyo: Hi-filler5000PJS) Foaming agent: Hydrogen peroxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.: Hydrogen peroxide concentration 30% by mass) Potassium hydroxide (Fujifilm Wako Pure Chemical Industries, Ltd.: Special grade)

[0056] (Production of geopolymer powder to be used as aggregate) First, a geopolymer foam was produced as the geopolymer powder to be used as aggregate. This geopolymer foam was crushed to obtain a geopolymer powder. It is assumed that the ends and scraps of the geopolymer foam will be collected and used as recycled materials. Here, examples of aggregates used to manufacture the above geopolymers assuming recycled materials include inorganic materials such as mica, wollastonite, chalk, talc, molochite, cordierite, basalt, feldspar, zircon, graphite, and borax, among which mica is preferably used. The content of the aggregate in the geopolymer is preferably 20 to 60%, more preferably 25 to 40%.

[0057] First, metakaolin was mixed with mica as an aggregate to form a powder raw material mixture. Potassium silicate, potassium hydroxide, and distilled water were mixed to prepare an alkali metal silicate aqueous solution (concentration 37%, pH = 14 or higher). The amount of aggregate mixed was 35.6% by mass relative to 100% by mass of the total of the aluminosilicate, alkali metal silicate and aggregate.

[0058] Next, 104 parts of an aqueous alkali metal silicate solution was mixed with 100 parts by mass of the powder raw material mixture, and the mixture was stirred at a stirring speed of 60 rpm to form a reaction slurry.

[0059] Next, 1.5 parts of a foaming agent (30% hydrogen peroxide solution) was added to the reaction slurry per 100 parts by mass, and the mixture was stirred with a stirring spatula at a stirring speed of 60 rpm for 1 minute to form a foamable composition. The foamable composition was then poured into any mold (molding die), the mold was sealed, and the mold was kept at a temperature of 60°C for 1 hour to obtain a geopolymer in-mold foam.

[0060] The geopolymer foam was then crushed using an automatic mortar (Nitto Kagaku ALG-200WD) and the particle size was separated using sieves with different mesh sizes to obtain crushed products 1 to 3.

[0061] [Table 1]

[0062] (Method of manufacturing geopolymer foam) First, aluminosilicate (metakaolin) and the geopolymer powder shown in Table 1 were mixed in the ratios shown in Tables 2 and 3 to form a powder raw material mixture. In addition, potassium silicate, potassium hydroxide, and distilled water as necessary were mixed to prepare an alkali metal silicate aqueous solution (potassium silicate concentration 37%, pH = 14 or higher).

[0063] Next, the powder raw material mixture and the alkali metal silicate aqueous solution were mixed in the ratios shown in Tables 2 and 3, and stirred at a stirring speed of 60 rpm to react the aluminosilicate and the alkali metal silicate to form a reaction slurry. Note that a foaming agent (30% hydrogen peroxide solution) was added to the reaction slurry in the ratios shown in Tables 2 and 3. Thereafter, the mixture was stirred for 1 minute at a stirring speed of 60 rpm using a stirring spatula to obtain a foaming agent composition.

[0064] The foamable composition was then poured into a mold (molding die) having a cylindrical molding space with a diameter of 90 mm and a height of 60 mm, the molding die was sealed, and the molding die was kept at a temperature of 60°C for 1 hour to completely react the aluminosilicate with the alkali metal silicate and to foam the reaction slurry, thereby obtaining a geopolymer foam. The geopolymer foam was then removed and kept at 60°C for about 1 day to dry it.

[0065] (Measurement method) (Average particle size) The average particle size of the geopolymer powder was measured using a HORIBA Laser Scattering Particle Size Distribution Partica LA-960 in accordance with JIS Z 8825: 2013. Specifically, the volume-based particle size distribution of the measurement subject was measured using the laser diffraction scattering method, and the volume average diameter was calculated as the average particle size.

[0066] (viscosity) The viscosity of the reaction slurry was measured using an ATAGO VISCO manufactured by Atago. Specifically, 60 mL of reaction slurry was placed in a 90 mL polystyrene cup, and the viscosity of the slurry was measured when it was stirred at 6 rpm using a spindle with a measurement range of A3. The viscosity was measured by measuring the viscosity of the reaction slurry immediately after mixing the aluminosilicate, geopolymer powder (powder raw material mixture), and alkali metal silicate aqueous solution, and before heating.

[0067] (Molded object density) The density of the geopolymer foam was calculated by measuring the apparent volume and weight of a sample from which the skin of the foam (the part molded adjacent to the mold) had been removed, and then dividing the weight by the apparent volume to convert it into units.

[0068] (Maximum bubble diameter) The maximum bubble diameter of the geopolymer foam was measured by projecting an arbitrary portion of the circular cut surface of the cylindrical sample without the skin at a magnification of 20 times, measuring the maximum diameter of each bubble, and taking the average of the five largest maximum diameters.

[0069] (Maximum stress) The compressive strength (maximum point stress) of the geopolymer foam was measured using Shimadzu Corporation's "Autograph AG-500B" as the measuring device, as follows. First, a cylindrical measuring sample with a diameter of 90 mm and a height of 50 mm, which does not have a skin on the top and bottom surfaces (bottom surfaces) in the column axis direction, was placed in the measuring device, and a compressive load was applied to the measuring sample in the direction that coincides with the height direction of the measuring sample, at a compression speed of 1 mm / min. The compression test was carried out until the displacement of the measuring sample reached 5 mm, and the maximum stress (maximum point stress) in this measurement was found, and this value was taken as the compressive strength.

[0070] <Examples 1 to 7> Geopolymer foam was obtained by using only geopolymer powder as aggregate in the ratio shown in Table 2. In the production of the obtained geopolymer foam, no excessive increase in viscosity of the reaction slurry was observed, and the foam could be obtained. In addition, the obtained geopolymer foam had excellent strength.

[0071] <Comparative Example 1> The crushed product 1 was used as the aggregate. The percentage (%) of particles with a particle size of 10 μm or less in the entire aggregate (geopolymer powder) was 5.2%, and the viscosity of the reaction slurry became too high to measure, so a geopolymer foam could not be obtained.

[0072] <Comparative Example 2> As aggregates, crushed products 2 and 3 were used. When the percentage (%) of particles with a diameter of 10 μm or less in the entire aggregate (geopolymer powder) was adjusted to 5.1%, the viscosity of the reaction slurry became too high to measure, and a geopolymer foam could not be obtained.

[0073] <Comparative Example 3> The crushed product 1 was used as the aggregate. The percentage (%) of particles with a particle size of 10 μm or less in the entire geopolymer powder (A) was 5.2%, and water was added to adjust the viscosity of the reaction slurry. The average maximum stress of the obtained geopolymer foam was 0.51 N / mm, and the strength was insufficient.

[0074] <Comparative Example 4> Crushed products 2 and 3 were used as aggregates. The percentage (%) of particles with a diameter of 10 μm or less in the aggregate (geopolymer powder) was adjusted to 5.1%, and water was added to adjust the viscosity of the reaction slurry. The average maximum stress of the obtained geopolymer foam was 0.42 N / mm, and the strength was insufficient.

[0075] <Comparison between Examples and Comparative Examples> As shown in Examples 1-7, it was confirmed that when the volume fraction of particles with a particle diameter of 10 μm or less in the geopolymer powder aggregate is 5% or less, the viscosity of the reaction slurry is good and a geopolymer foam with excellent strength is obtained.

[0076] On the other hand, as shown in Comparative Examples 1 and 2, when the volume ratio of particles with a particle diameter of 10 μm or less in the geopolymer powder aggregate was greater than 5%, the viscosity of the reaction slurry became so high that it was impossible to measure, making it difficult to obtain a geopolymer foam. Also, as shown in Comparative Examples 3 and 4, although it was possible to adjust the viscosity and form a cellular structure by adding water to the reaction slurry of Comparative Examples 1 and 2, it was confirmed that the strength of the geopolymer foam was insufficient.

[0077] [Table 2]

[0078] [Table 3]

Claims

1. A method for producing a geopolymer foam, comprising reacting an aluminosilicate with an alkali metal silicate in the presence of an aggregate to form a reaction slurry containing a geopolymer, and foaming the reaction slurry with a foaming agent to form a geopolymer foam having a large number of bubbles, the aggregate comprises geopolymer powder; The average particle size of the geopolymer powder is 30 to 500 μm; A method for producing a geopolymer foam, characterized in that the volume ratio of particles having a particle diameter of 10 μm or less in the geopolymer powder is 5% or less.

2. The method for producing a geopolymer foam according to claim 1, characterized in that the volume fraction of particles having a particle diameter of 200 μm or more in the geopolymer powder is 85% or less.

3. The method for producing a geopolymer foam according to claim 1 or 2, characterized in that the geopolymer powder is a powder obtained by pulverizing a geopolymer foam.

Citation Information

Patent Citations

  • Geopolymer composites and structures formed therefrom

    JP2008543701A

  • Geopolymer composition and method for producing the same

    JP2012188329A

  • Geopolymer-based inorganic foam

    JP2020511387A

  • Porous geopolymer materials

    US20130055924A1

  • Sintered geopolymer compositions and articles

    WO2020056470A1